IDENTIFICANDO OS DETERMINANTES DA EFICIÊNCIA TÉCNICA NA PRODUÇÃO DE CAFÉ DE MONTANHA EM MINAS GERAIS - NASCIMENTO, Ana Carolina Campana; NASCIMENTO, Moysés; BARROSO, Lais Mayara Azevedo; SOUSA, Lucas Oliveira; BRAGA, Marcelo José (Brazilian Journal of Biometrics, 2017)
The main objective of this study was to analyze the technical efficiency of mountain coffee producers of Minas Gerais and to investigate factors that influence it. The technical efficiency of production units was measured using the Data Envelopment Analysis (DEA) and then, based on quantile regression models, we identified the factors that explain the efficiency scores. For this, we used data of 786 producers of Minas Gerais, for the year 2009. The main results indicate that most producers have operated inefficiently and that the factors that influence the level of efficiency are not the same for all producers.